What's Wrong with These Pictures? Race, Narratives of Admission, and the Liberal Self-Representations of Historically White Colleges and Universities - David Roediger (Washington University Journal of Law & Policy, 2005)
This Essay focuses on the interpretation of several iconic images used to represent racial inclusion at what the sociologist Eduardo Bonilla-Silva has tellingly called “historically white colleges and universities.” All of the images come from schools in the Midwest, and, churlishly enough, a memorial in the law school publishing this Journal comes in for the most extended criticism. In mitigation, I conclude with discussions of my own institution, University of Illinois, whose use of a racist caricature of American Indians to rally its fans now makes it the (pun intended) chief offender among Midwestern universities where race and representation are concerned. However, while brief exploration of the connection between Illinois’s hideous anti-Indian symbolism and its professed racial liberalism ends this Essay, the larger focus is on images professedly designed not to entertain fans, but to “admit” students of color into the historically white institutions. The liberal narrative of admission that welcomes students of color to historically white universities comes, the Essay argues, at the high price of effacing the exclusionary past and present of such institutions. Thus, the notion recently advanced at Illinois that a racist sports symbol can be put into the service—or somehow has always been in the service—of multiracial education represents not so much a sharp break with the ways the historically white, but confidently liberal, university represents itself as an elaboration of such views.
Keywords: Critical race theory; College student recruitment; Universities & colleges -- Admission